Unleashing the power of teacher’s wellbeing and selfcare - Abou Assali, Mouna; Al Abdouli, Khameis (Research Journal in Advanced Humanities, 2024)
Teachers’ personal and professional life depends heavily on their health and self-care. This article examines the value of teacher wellbeing and self-care, educators’ difficulties, and the possible advantages of putting their physical, mental, and emotional health first. The many challenges teachers face can have an impact on their wellness. Teachers frequently struggle to maintain a healthy work-life balance because of the hard job, long hours, and time limits. Additionally, the emotional demands of the job, such as handling difficult circumstances or managing student behavior problems, might result in elevated stress levels. These issues are made more difficult by scarce resources, a lack of support networks, and a culture that puts teacher wellbeing last. Schools and higher tertiary institutions may establish a happy and encouraging environment that improves overall student results by recognizing and addressing the wellbeing of instructors. This paper will encourage teachers to release the power of self-care and prioritize their wellbeing. This research paper focused on the benefits of teachers’ wellbeing and self-care, the common challenges teachers face, and strategies for promoting teachers’ wellbeing and self-care. A qualitative secondary data research approach was used in data collection, which uncovered numerous elements that significantly impact teachers’ wellbeing.